Development of Low-Cost High-Power Sinusoidal Function Generator for Driving a Single Tone Wave into Speaker using Arduino Uno and 2N3055 - Adimas Wicaksana; Sulanjari Sulanjari (Piston: Journal of Technical Engineering, 2019)
Function generator is one of the most important equipment in electronics testing. However its cost can be quite prohibitive. In this work we will study how to transform a square wave generated by Arduino into a sine wave by using filter/amplifier based on 2N3055, thus enabling low-cost high-power function generator. Said function generator will be shown to  be capable of producing sine wave with frequency between 500Hz-10KHz. With proper tuning it is capable of achieving up to 0.6% accuracy within the desired value.